Pressurized liquid extraction as a green technique for bioactive compounds recovery from Momordica charantia leaves - Gabriell J. R․ Rocha; Ana C․ Aguiar; Cátia O. G․ Abud; Paula B․ Pertuzatti; Klicia A․ Sampaio; Julia T․ Paula (Applied Food Research)
Momordica charantia L., an unconventional food plant, has long been used in traditional medicine to treat conditions such as diabetes and digestive disorders. This study employed pressurized liquid extraction (PLE) to recover bioactive compounds from M. charantia, examining the effects of different extraction parameters, including solvent type (ethanol, 50 % hydroalcoholic mixture, water), temperature (40, 50, 60 °C), and solvent flow rate (1, 2, 3 g/min). The extracts were analyzed for global yield, total phenolic content (TPC), total flavonoid content (TFC), chlorophyll content, and antioxidant capacity (DPPH and ABTS assays). Phenolic compounds were identified through high-performance liquid chromatography coupled with electrospray ionization mass spectrometry (HPLC-DAD-ESI-MSn). PLE using 50 % hydroalcoholic solvent at 60 °C yielded the highest TPC (14.4 ± 0.3 mg GAE/g sample) and TFC (6.6 ± 0.1 mg QE/g sample). Ethanolic PLE extracts exhibited higher antioxidant activity in the DPPH assay, while aqueous extracts showed greater activity in the ABTS assay, likely reflecting differences in chemical composition. A total of 24 phenolic compounds, including phenolic acids, flavanones, and flavonols, were identified using HPLC-DAD-ESI-MSn, with profiles varying according to the solvent type used for PLE. In the modeling of PLE kinetics curves, the Spline model identified three distinct stages in the extraction process. Optimal conditions were determined to be a temperature of 60 °C and a solvent flow rate of 2 g/min, which maximized bioactive compound extraction. These results highlight the potential of PLE as an efficient method for valorizing M. charantia through the extraction of bioactive compounds.